Apnea in a Two-Week-Old Infant Infected with SARS-CoV-2 and Influenza B - Radhika Maddali; Kelly L. Cervellione; Lily Q. Lew (Case Reports in Pediatrics)
Paucity of data exists on presenting symptoms and outcomes in infants with COVID-19. Reports of coinfection with COVID-19 and influenza B are sparse in the literature. Coinfection was uncovered during evaluation of neonatal apnea. Apnea has been reported in infants with SARS-CoV-2 infection, though it is rare. We describe a 2-week-old healthy term infant presenting with apnea and coinfection. The infant had a mild clinical course and complete recovery.